Exploring the Relativity of Deviance - Kane, Laura; Pike, Elizabeth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2021)
Students in Criminology courses are familiar with positivist theories of crime that assume the behavior is wrong and attempt to provide explanations for that behavior. This Social Deviance and Social Control course is required for both Sociology and Criminology majors and attempts to broaden students’ horizons regarding understanding why one might act deviantly, have deviant opinions, and have deviant conditions. Explaining the socially constructed nature of deviance is a major outcome for the course, particularly as one cannot explain a deviant condition (e.g., a disability with which one is born) through positive explanations of behavior. The first homework of the semester allows students to conduct research on what/who their friends believe is deviant, compare those answers to those of classmates, compare those answers to a 1960s survey to document change, and finally explore how one social institution, the media, impacts our understanding of what is deviant. The assignment described below includes a homework assignment outside of class, classroom discussion, and a listening experience to a podcast episode about vaccines (with accompanying transcript) with more class discussion. The wrap up of the assignment sets up students to be excited to explore the socially constructed nature of deviance in many topics in the weeks to come.